Pengaruh Penilaian Produk, Gratis Ongkos Kirim, dan Potongan Harga terhadap Keputusan Pembelian Pakaian Pria di E-Commerce Shopee di Kota Bengkulu - Dwitama, Yosep; Syofian, Syofian; Safrianti, Sintia (https://jurnal.binamandiri.ac.id/, 2024)
This research aims to determine the influence of product ratings, free shipping, and price discounts on men's clothing purchasing decisions at Shopee e-commerce in Bengkulu City. This research is quantitative. Research the population of consumers who have made purchasing decisions on the Shopee application. The sample in this research uses the Hair formula, namely n×5. This research has 24 indicators with 24×5=120 respondents, so the number of respondents is sufficient to represent the study population. Data was obtained from respondents filling out a questionnaire (Google Form) using purposive sampling as a sampling technique. The analytical method used is multiple linear regression analysis and hypothesis testing t-test and F-test using SPSS 22 program tools. The results of the research show that: 1.) there is a significant influence of product assessment on the decision to purchase men's clothing at Shopee e-commerce in Bengkulu City; 2.) free shipping has a significant effect on purchasing decisions for men's clothing on Shopee e-commerce in Bengkulu City; 3.) price discounts influence the decision to purchase men's clothing on Shopee e-commerce in Bengkulu City; 4.) product evaluation, free shipping, and price discounts on men's clothing purchasing decisions on Shopee e-commerce in Bengkulu City together have a simultaneous influence.